(untitled) (Texas Journal of Medical Science, 2023)
Vision is the ability to perceive light stimuli through the eyes, transport information to the brain, which subsequently interprets it in order to relate to the world around us. In this way we can correctly distinguish between colors, shapes, movements and distances. Vision is an essential tool for day-to-day life and its loss leads to a reduction in the person’s independence as well as in their quality of life.